2019
DOI: 10.1002/jbm.b.34430
|View full text |Cite
|
Sign up to set email alerts
|

Injectable calcium phosphate foams for the delivery of Pitavastatin as osteogenic and angiogenic agent

Abstract: Apatitic bone cements have been used as a clinical bone substitutes and drug delivery vehicles for therapeutic agents in orthopedic applications. This has led to their combination with different drugs with known ability to foster bone formation. Recent studies have evaluated Simvastatin for its role in enhanced bone regeneration, but its lipophilicity hampers incorporation and release to and from the bone graft. In this study, injectable calcium phosphate foams (i‐CPF) based on α‐tricalcium phosphate were load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Furthermore, the cumulative release kinetics for both curcumin and vitamin K2 are best fitted with the Korsmeyer–Peppas model, to further analyze the drug release kinetics. The diffusion exponent or n value from the Korsmeyer-Peppas plot for are less than 0.45 for both curcumin and vitamin K2 loaded Ti implants, which corresponds to Fickian diffusion mechanism . Although this model has been previously used to define drug release profiles from polymeric matrix, nowadays various studies have reported its application in porous ceramics drug delivery system.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the cumulative release kinetics for both curcumin and vitamin K2 are best fitted with the Korsmeyer–Peppas model, to further analyze the drug release kinetics. The diffusion exponent or n value from the Korsmeyer-Peppas plot for are less than 0.45 for both curcumin and vitamin K2 loaded Ti implants, which corresponds to Fickian diffusion mechanism . Although this model has been previously used to define drug release profiles from polymeric matrix, nowadays various studies have reported its application in porous ceramics drug delivery system.…”
Section: Discussionmentioning
confidence: 98%
“…The diffusion exponent or n value from the Korsmeyer-Peppas plot for are less than 0.45 for both curcumin and vitamin K2 loaded Ti implants, which corresponds to Fickian diffusion mechanism. 38 Although this model has been previously used to define drug release profiles from polymeric matrix, nowadays various studies have reported its application in porous ceramics drug delivery system. Dissolution of HA coating is an important parameter that not only regulates the durability and stability of the coating but also controls the drug release kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Pitavastatin enhances the osteoblastic activity by several mechanisms, as mentioned previously. It induces the production of several vascular endothelial growth factors and stimulates BMP-2 and osteocalcin production as mentioned elsewhere [98].…”
Section: Histological Assaymentioning
confidence: 90%
“…The foams released pitavastatin ( Figure 3) by an initial burst. In vitro, pitavastatin delivery increased BMP-2 and VEGF expression indicating advantageous osteogenic and angiogenic effects [60]. Furthermore, pravastatin ( Figure 3) can be used in bone regenerative applications as well.…”
Section: Calcium Phosphatesmentioning
confidence: 99%